An update on the role of complement in hepatocellular carcinoma - Xiao, Zhijie; Yeung, Charlie Lot Sum; Yam, Judy Wai Ping; Mao, Xiaowen (Frontiers in Immunology, 2022)
As a main producer of the complement, the environment in liver is greatly affected by complement system. Though the complement is considered as a nonself discrimination, remarkable studies have revealed the tight association between the improper complement activation in the tumor initiation and progression. As complement activation predominately occurs within the liver, the pro-tumorigenic role of complement system may contribute to the development of hepatocellular carcinoma (HCC). Improvement in the understanding of the molecular targets involved in complement-mediated tumor development, metastasis, and tumor-promoting inflammation in HCC would certainly aid the development of better treatments. This minireview is focused on the recent findings of the pro-tumorigenic role of complement system in HCC.